2005
DOI: 10.1159/000083502
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Whole Body Endogenous Nitric Oxide Production in Patients with Primary Pulmonary Hypertension

Abstract: Impaired pulmonary release of nitric oxide (NO) is one of the characteristic phenotypic changes of vascular cells in pulmonary hypertension. The aim of this study was to determine nitric oxide synthase (NOS)-dependent whole body NO production in patients with primary pulmonary hypertension. NOS-dependent whole body NO production was assessed by giving an intravenous infusion of L-[15N]2-arginine (50 µmol/min for 30 min) and measuring isotopic urinary enrichment of 15N-nitrite a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 28 publications
(20 reference statements)
0
26
0
Order By: Relevance
“…Although it is possible that this variable influenced the statistical analysis independent of NO, this is an unlikely scenario. First, the use of a ratio between a biomarker and urine Cr is a standard method to adjust for urinary dilution (28)(29)(30)(31). Second, in multivariate analyses that included estimated GFR, baseline urine NO/Cr remained highly predictive of better outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is possible that this variable influenced the statistical analysis independent of NO, this is an unlikely scenario. First, the use of a ratio between a biomarker and urine Cr is a standard method to adjust for urinary dilution (28)(29)(30)(31). Second, in multivariate analyses that included estimated GFR, baseline urine NO/Cr remained highly predictive of better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The Cr results obtained were also used to evaluate urine desmosine in these patients; those results have been reported elsewhere (27). The ratio of urine NO to urine Cr (NO/Cr) was used in the statistical analyses to control for urine dilution, a standard method when evaluating urine biomarkers (28)(29)(30)(31). Analyses using urine NO without Cr correction were performed for comparison.…”
Section: No and Cr Measurementsmentioning
confidence: 99%
“…A recent study has shown a decrease in nitric oxide (NO) production after intravenous injection of L -arginine, a precursor for NO synthesis, in patients with primary PH, suggesting a possibility of impaired NO-mediated signaling [1]. Since impairment of NO-mediated signaling is considered as one of the causes of PH during the imbalance between endothelial mediators with opposing actions on pulmonary vasculature, inhaled NO has been used in the treatment of patients with PH.…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms are mediated by 1 or more molecular and cellular processes, including the following: reduced prostacyclin availability caused by diminished endothelial cell prostacyclin synthase activity 25 ; elevated endothelin levels resulting from enhanced production and reduced pulmonary clearance [26][27][28] ; decreased nitric oxide synthase expression 29,30 ; elevated plasma levels and low platelet 5-hydoxytryptamine levels 31 ; down-regulation of voltage-gated potassium (eg, Kv1.5) channels of pulmonary vascular smooth muscle cells 32,33 ; activity of autoantibodies and proinflammatory cytokines 34,35 ; and prothrombotic states arising from endothelial, coagulation, and fibrinolytic cascade and platelet dysfunction. [36][37][38][39] These abnormalities give rise to a predisposition to vasoconstriction over vasodilation of the pulmonary vascu-FIGURE 1.…”
Section: Molecular and Cellular Mechanismsmentioning
confidence: 99%